Pemberdayaan Kelompok PKK melalui Pelatihan Pengolahan Keripik Ikan Lele di Desa Belepanawa - Tukan, Maria Magdalena Nona Motu (Universitas Aufa Royhan Di Kota Padangsidipuan, 2026)
Catfish (Clarias sp.) is a popular freshwater commodity. Currently, processed catfish products are not widely distributed in the community. This is due to various factors, such as the lack of education and socialization about processed catfish, the lack of public knowledge about the nutritional content of processed catfish foods, and how to diversify processed catfish that can be done in the community. This activity aims to provide understanding and training to PKK groups on processing catfish into processed catfish chips and good packaging techniques to increase the selling value of the product. A training activity on catfish chip snack products was held in Blepanawa Village, Demon Pagong District, East Flores Regency. The training method used was hands-on practice or demonstration, where participants were actively involved in every stage of the production process. This approach was considered effective because the community learned through direct experience, starting from processing raw materials to producing ready-to-sell products. Overall, this training activity had a positive impact on the PKK group in Belepanawa Village. Participants, mostly housewives and small business owners, became more skilled, creative, and motivated to utilize the potential of local fish as a raw material for high-value products